Design of diketopyrrolopyrrole chromophores applicable as sensitizers in dye-sensitized photovoltaic windows for green houses. (November 2016) - Duvva, Naresh; Raptis, Dimitrios; Kumar, Challuri Vijay; Koukaras, Emmanuel N.; Giribabu, Lingamallu; Lianos, Panagiotis
Abstract: Three diketopyrrolopyrrole D-π-A chromophores have been designed as sensitizers in dye-sensitized solar cells. Design was aided by DFT and Time Resolved TFT theoretical calculations. The prime goal was to obtain dyes, which do not absorb light in the spectral zones that favor plant growth, so that the dyes may act as sensitizers in photovoltaic windows for green houses. This prime goal was accomplished to a very satisfactory degree. When applied to dye-sensitized solar cell devices using I3 − /I − redox, the three dyes demonstrated a diverse behavior. The most efficient solar cells were obtained with a symmetric dye employing two cyanoacrylic acid acceptors. Graphical abstract: Highlights: Design of diketopyrrolopyrrole D-π-A dyes as sensitizers for dye-sensitized solar cells. Design assisted by theoretical calculations. Dyes absorb light outside the spectral zones that favor plant growth. These dyes may act as sensitizers in photovoltaic windows for green houses.